A biomedical open knowledge network harnesses the power of AI to understand deep human biology. Issue 1 (31st March 2022) - Baranzini, Sergio E.; Börner, Katy; Morris, John; Nelson, Charlotte A.; Soman, Karthik; Schleimer, Erica; Keiser, Michael; Musen, Mark; Pearce, Roger; Reza, Tahsin; Smith, Brett; Herr, Bruce W.; et al.
Abstract: Knowledge representation and reasoning (KR&R) has been successfully implemented in many fields to enable computers to solve complex problems with AI methods. However, its application to biomedicine has been lagging in part due to the daunting complexity of molecular and cellular pathways that govern human physiology and pathology. In this article, we describe concrete uses of Scalable PrecisiOn Medicine Knowledge Engine (SPOKE), an open knowledge network that connects curated information from thirty‐seven specialized and human‐curated databases into a single property graph, with 3 million nodes and 15 million edges to date. Applications discussed in this article include drug discovery, COVID‐19 research and chronic disease diagnosis, and management.